Human resource & administration department integrity and governance department of Kedah Darul Aman / Wan Mohd Muaz Mohd Navawi - Mohd Navawi, Wan Mohd Muaz (Univesiti Teknologi MARA Cawangan Sarawak, 2015)
This is a first week of practical training at Integrity Department. The trainee had registered to Human Resource Department before the trainee being placed into Kedah’s Integrity and Governance unit. As usual, any new entrant will be given short briefing regarding on the organization and be introduced to all staff. On second day, the trainee began the task byrechecking the attendance list of participants of “Bengkel Pemantapan Integriti” that been participated by all Kedah’s Local and Land council . The trainee must get the confirmation of participants' attendance from the particular organization by sent the attendance list through fax. On the next day, the trainee called all the Kedah’s Local and Land Council to informed new date of “Bengkel Pemantapan Integriti” and update the attendance list by classified the name based on gender and unit before the trainee received the confirmation attendance list by following day.